2012
DOI: 10.1071/he12063
|View full text |Cite
|
Sign up to set email alerts
|

Australian athletes' health behaviours and perceptions of role modelling and marketing of unhealthy products

Abstract: Elite athletes are receptive to supporting health promotion through sport and many are not in agreement with the promotion of unhealthy products in sport or by sports people. Improving elite athletes' health behaviours would benefit not only the individual but also health promotion within elite sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…Grall-Bronnec's study identified that betting on your own team was a risk factor of problem gambling and although that study included only athletes in team ball sports, this association still could be suspected to increase gambling problems more in team players ( Grall-Bronnec et al, 2016 ), but no studies have addressed solely elite athletes on a national team level. Previous data has indicated that, e.g., binge alcohol drinking, smoking and involvement in alcohol commercials are more common in team sports than in individual sports ( Grunseit et al, 2012 ), and the present study rather indicates that this would not necessarily be the case for gambling. The proportion of problem gamblers in team sports and individual sports was close to identical, making it unlikely that a difference would be seen even in a larger data set.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Grall-Bronnec's study identified that betting on your own team was a risk factor of problem gambling and although that study included only athletes in team ball sports, this association still could be suspected to increase gambling problems more in team players ( Grall-Bronnec et al, 2016 ), but no studies have addressed solely elite athletes on a national team level. Previous data has indicated that, e.g., binge alcohol drinking, smoking and involvement in alcohol commercials are more common in team sports than in individual sports ( Grunseit et al, 2012 ), and the present study rather indicates that this would not necessarily be the case for gambling. The proportion of problem gamblers in team sports and individual sports was close to identical, making it unlikely that a difference would be seen even in a larger data set.…”
Section: Discussioncontrasting
confidence: 49%
“…In recent years, mental health issues specific to athletes, including addictive disorders, have been highlighted. In general, it has been suggested that the prevalence of mental health problems in elite sports seems to mirror society as a whole ( Rice et al, 2016 ), however, although a sparsely studied area, participation in team sports has been described as a particular risk factor of addictive behaviour ( Grunseit et al, 2012 ). More specifically, higher prevalence of risky drinking in athletes was explained by higher rates of risk-taking and sensation-seeking behaviour ( Mastroleo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…20 Previous research has shown that athletes who play team sports are more likely to be accepting of junk food and alcohol advertising in sport, compared with individual athletes, and also have higher rates of smoking and excessive alcohol consumption. 11 Encouraging players to champion healthy behaviours through media campaigns and to refrain from associating themselves with unhealthy products and brands could reduce the opportunities for unhealthy sports sponsorship, thus achieving future desired reductions in its prevalence. However, this must be coupled with support and action from key sport and policy decision makers.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Unhealthy food and beverage products are promoted at sports clubs at both the elite and the community club level, often through sponsorship. 8,11 Evidence shows that, at least at the local sports club level, sponsorship influences children's recall and impressions of these companies; they perceived food companies as 'cool', as well as being more likely to consider such sponsors when making food and beverage purchases. 12 Parents and the junior sporting community have reported strong support for the introduction of policy interventions to limit unhealthy food and beverage company sponsorship of children's sport.…”
Section: Introductionmentioning
confidence: 99%
“…Females in this study were significantly more likely to want more healthy food options available at their club than males. While the promotion of food and beverages has been explored in some studies [65,66] and another has explored stakeholders views [23]; there is limited research exploring sportspeople's attitudes towards the availability of healthy food in sports clubs, however Australian female athletes have been found to be more opposed to unhealthy food advertising in sport than male athletes [67] and females to have a stronger interest in healthy eating than males [68].…”
Section: Discussionmentioning
confidence: 99%